MENINGKATKAN PENGAMBILAN KEPUTUSAN MELALUI VIDEO PEMBELAJARAN BILINGUAL DENGAN CAPCUT - Ismi, Ismi Putri Intan; Netriwati; Salsabila; Fadly Nendra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This development research aims to develop a bilingual learning video based on CapCut to improve valid and effective decision making to facilitate students and educators in the learning process. This study uses a research and development type of research with the DDDE (Decide, Design, Develop, and Evaluate) model. The data analysis techniques used are small-scale validity tests and N-Gain tests. The test subjects in this study were semester 2 students of the Mathematics Education Study Program, Faculty of Tarbiyah and Teacher Training, Raden Intan State Islamic University, Lampung. The results of the validity test on a small scale show that the instruments used are valid and reliable. The assessment of the effectiveness test using N-Gain on the test obtained a score of 0.439 with the criteria of "moderate". The results of this study indicate that the bilingual learning video based on CapCut has been valid and effective for use in the learning process.